Strategies for supporting the conservation of secondary tropical forests embedded in modified landscapes - Brancalion, Pedro Henrique Santin; Viani, Ricardo Augusto Gorne; Rodrigues, Ricardo Ribeiro; César, Ricardo Gomes (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2012)
While research demonstrates the utmost importance of tropical secondary forests for biodiversity conservation and the provision of ecosystem services, these forests are being continuously converted for agriculture, as well as being degraded by a variety of human-induced disturbances. Therefore, in addition to understanding the formation, functioning, and development of tropical secondary forests, it is also vital that the protection and maturation of secondary forests become a focus of public policies aimed at maximizing the conservation of biodiversity and provision of ecosystem services in human-modified landscapes. Here we review the drivers of the conversion and degradation of tropical secondary forests in human-dominated Brazilian landscapes. Based on this review, and examples of successful reforestation initiatives, we propose policy options based on ecological, socioeconomic, and legal aspects of forest management and conservation for two contrasting scenarios – high- and low-modified tropical landscapes, exemplified by the Brazilian biomes of the Atlantic Forest and Amazon respectively. This framework provides a new and more holistic approach for sustaining and promoting a favorable outlook for the conservation of secondary forests in Brazil and across the tropics in general.
Keywords: Atlantic Forest; Amazon; Secondary forests; Biodiversity; Deforestation; Ecological succession